2015
DOI: 10.1007/s10586-015-0472-6
|View full text |Cite|
|
Sign up to set email alerts
|

Large scale graph processing systems: survey and an experimental evaluation

Abstract: Graph is a fundamental data structure that captures relationships between different data entities. In practice, graphs are widely used for modeling complicated data in different application domains such as social networks, protein networks, transportation networks, bibliographical networks, knowledge bases and many more. Currently, graphs with millions and billions of nodes and edges have become very common. In principle, graph analytics is an important big data discovery technique. Therefore, with the increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(53 citation statements)
references
References 32 publications
(41 reference statements)
0
49
1
1
Order By: Relevance
“…The execution time is faster in block-centric, but the overall response time is slower due to overheads discussed in Section 5.1. [13] It was previously reported that GraphX has the best performance across all systems [13]. Our results contradicts this assertion.…”
Section: Related Workcontrasting
confidence: 56%
“…The execution time is faster in block-centric, but the overall response time is slower due to overheads discussed in Section 5.1. [13] It was previously reported that GraphX has the best performance across all systems [13]. Our results contradicts this assertion.…”
Section: Related Workcontrasting
confidence: 56%
“…There are also numerous surveys in the literature studying different topics related to graph processing. Examples include surveys on query languages for graph database systems and RDF engines [10,44,47], graph algorithms [3,45,53,97], graph processing systems [16,61], and visualization [24,95]. These surveys do not study how users use the technologies in practice.…”
Section: Related Workmentioning
confidence: 99%
“…Simple graphs Attributed graphs Keyword Location Temporal Influence (weight) Profile k-core [175,46,15,66] (P. 1, 2, 3, 4, 5) [61,58] (P. 6) [60,65,185,221] (P. 7,8,9) [129] (P. 10) [127,128,30,215,21,126] (P. 12,13) [31] (P. 14) k-truss [98,6,101] (P. 15,16) [102] (P. 17) -- [216] (P. 18) k-clique [45,205,195,187] (P. 19,20,21,22) -- [125] Example 2 Let us reconsider the graph G in Fig. 2(a).…”
Section: Metricmentioning
confidence: 99%